Pseudotachylytes from Langhovde and Skarvsnes in the Lützow-Holm Complex, East Antarctica, and their conditions of formation - Toyoshima, Tsuyoshi; Ishikawa, Masahiro; Kitano, Ippei; Katori, Takuma; Hokada, Tomokazu (2019)
The Tenth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Wed. 4 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object